A Study of Forecasting Practices in Supply Chain Management - Albarune, Abu Raihan Bhuiyan; Habib, Dr. Md. Mamun (International Journal of Supply Chain Management, 2015)
This study demonstrates forecasting practices in supply chain management (SCM) at various areas, particularly Pharmaceuticals, Retail, and FMCG. The authors depicts the scenario of forecasting practices based on secondary data and represents SCM role, demand management, collaborative coordination, etc. In addition to this, the study reveals the limitation and few practical solutions on forecasting to be useful in the organization. Consequently the author describes recommendation and proposes a model on forecast management model. Though this paper highlights case studies,however, it unlocks further frontiers for the prospective researchers as well as practitioners in order to apply forecasting techniques.